2020
DOI: 10.1088/1748-605x/ab7b3c
|View full text |Cite
|
Sign up to set email alerts
|

Fiber diameter, porosity and functional group gradients in electrospun scaffolds

Abstract: People interested in the research are advised to contact the author for the final version of the publication, or visit the DOI to the publisher's website. • The final author version and the galley proof are versions of the publication after peer review. • The final published version features the final layout of the paper including the volume, issue and page numbers. Link to publication General rights Copyright and moral rights for the publications made accessible in the public portal are retained by the author… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 68 publications
0
6
0
Order By: Relevance
“…Common remedies include the use of salt-based porogens [1][2][3][4] or sacrificial fibers [1,2,5,6] that should create the space needed for cell ingress and tissue development. More recently, complex gradients are being engineered into state-of-the-art scaffolds [7][8][9][10][11][12] to more closely mimic biological structures or to enable high-throughput screening. Despite these advances, characterization methods that provide comprehensive, spatially-resolved quantification of porosity are still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Common remedies include the use of salt-based porogens [1][2][3][4] or sacrificial fibers [1,2,5,6] that should create the space needed for cell ingress and tissue development. More recently, complex gradients are being engineered into state-of-the-art scaffolds [7][8][9][10][11][12] to more closely mimic biological structures or to enable high-throughput screening. Despite these advances, characterization methods that provide comprehensive, spatially-resolved quantification of porosity are still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…A two-dimensional map of the epitope-presenting substrate was achieved and cells adjusted their adhesion behavior according to the density of the RGD-epitope on the substrate (Scheme ). This versatile platform could be employed for bio and tissue engineering, in which spatial control over cell growth can be achieved on an anisotropic distribution of bioactive molecules, mimicking the ECM in certain aspects. …”
Section: Introductionmentioning
confidence: 99%
“…Recently, Zonderland added functionalized poly(ethylene glycol) additives to the polymer solution to create a scaffold with an in-depth gradient of functional groups, which can potentially be used in a wide variety of polymer solutions to couple peptides and proteins to electrospun scaffolds. 116 Surface coating is another common method. It has been reported that fibers coated with natural materials could exhibit better biological behaviors such as infiltration and homogeneous distribution of cells 117,118 and show potential for periodontal ligament regeneration.…”
Section: Surface Modificationmentioning
confidence: 99%